2015
DOI: 10.1364/oe.23.030801
|View full text |Cite
|
Sign up to set email alerts
|

256 Tbit/s/ch (640 Gbaud) polarization-multiplexed DQPSK non-coherent Nyquist pulse transmission over 525 km

Abstract: We demonstrate a single-channel 2.56 Tbit/s polarization-multiplexed DQPSK transmission using 640 Gbaud non-coherent optical Nyquist pulses. By virtue of a large tolerance to polarization-mode dispersion, the detrimental depolarization-induced crosstalk was reduced by 3.8 dB compared with RZ pulses. As a result, the transmission distance was substantially extended to 525 km compared with the distance of 300 km obtained with a Gaussian pulse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Due to the rectangular-shaped spectrum and sinc-shaped temporal waveform, Nyquist pulses have high value in modern communication technology, from electronic communications to optical communications and ultrafast science. For example, in the field of optical communications, [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Nyquist pulses can increase the bandwidth of the systems. [16] Various studies on Nyquist pulses have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rectangular-shaped spectrum and sinc-shaped temporal waveform, Nyquist pulses have high value in modern communication technology, from electronic communications to optical communications and ultrafast science. For example, in the field of optical communications, [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Nyquist pulses can increase the bandwidth of the systems. [16] Various studies on Nyquist pulses have been reported.…”
Section: Introductionmentioning
confidence: 99%